Lipid body formation by Thraustochytrium aureum (ATCC 34304) in response to cell age - Jeh, Eun-Jin; Kumaran, Rangarajulu Senthil; Hur, Byung-Ki (The Korean journal of chemical engineering, 2008)
The heterotrophic marine protist, Thraustochytrium aureum produces substantial amounts of polyunsaturated fatty acids (PUFAs). In the present investigation, changes in the lipid and fatty acid profiles of T. aureum were studied according to the culture age. T. aureum was grown in artificial sea water medium for 10 days at 25 °C in shake culture condition. One to 10 day old cell samples were analyzed for cell biomass production, total lipid content, fatty acid profile and lipid body formation. In all the samples tested, total lipid production was found to be directly proportional to the dry cell weight of T. aureum . In the early phase of cell growth, cell biomass production, lipid content and glucose consumption were found to be higher. Thin layer chromatographic analysis (TLC) of lipids showed the presence of triacylglycerol (TAG; 169 mg/g, 90%), phospholipids (PL; 83 mg/g, 66%) and sterol (ST; 6 mg/g, 5%), which were recorded at maximum levels in the early growth phase of the cells. The composition of PUFAs and saturated fatty acids (SFAs) of the cell biomass and lipid class components (TAG and PL) was identified by gas chromatographic analysis (GC). In the early phase of cell growth, production of PUFAs in the total fatty acids was found to have attained maximum levels (61.3%) in which docosahexaenoic acid alone showed higher content of occurrence (99.0 mg/g in total lipid; 65.2 mg/g in TAG and 41.0 mg/g in PL). In the middle phase of cell growth, palmitic acid production was found to be higher (36.7 mg/g in total lipid; 31.3 mg/g in TAG and 12.6 mg/g in PL). Transmission electron microscopic studies of the cells showed the presence of a membrane around the lipid bodies in the early phase of cell growth. TAG and PL were actively involved in the formation of lipid bodies in the cells of T. aureum . Large-sized lipid bodies accumulated in 3 day old cells which were then fragmented into smaller bodies in the late growth phase.